ChemInform Abstract: Atomic Structure of Defects in Anion‐Deficient Perovskite‐Based Ferrites with a Crystallographic Shear Structure. Issue 16 (22nd April 2014) - Batuk, Maria; Turner, Stuart; Abakumov, Artem M.; Batuk, Dmitry; Hadermann, Joke; Van Tendeloo, Gustaaf
Abstract Pb2Sr2Bi2Fe6O16 is prepared by solid state reaction of PbO, SrCO3, Bi2O3, and Fe2O3 (annealing in air at 750 and 850 °C for 24 h each).